Effect of Timber, Palm Oil, and Gold Output on GNI in Indonesia in the Maqashid Framework - Sulistya Rusgianto; Akhmad Kusuma Wardhana; Hasna Fauziana (FKIP Universitas Lampung, 2022)
This study had a purpose to observe if the natural resources production had a significant impact on GNI of Indonesia. this study also observed if the management of natural resources in Indonesia has been appropriate based on maqashid sharia principle. This study used secondary data gathered from Faostat for palm oil and Roundwood coniferous production, and the world bank for data about gross national income (GNI) and total gold reserved. The data was collected using purposive sampling from Indonesia, starting from 1970 to 2019. The data were analyzed using vector error correction model method and processed by Eviews version 10. The result showed that palm oil and Roundwood coniferous productions had no significant effect to GNI. However, ouput of gold production had a significant effect to GNI of Indonesia. This study also showed that in the case of palm oil and Roundwood production, the way they had obtained was not appropriate according to the principle of maqashid sharia. In the case of palm tree plantation, the plantation could damage the nature and affect the social economy of the local people. In the case of Roundwood coniferous production, there was may illegal logging to increase the output.